Analysis of factors limiting the import-substituting effect of cluster development in the agro-industrial complex - Moga Irina S.; Baykov Fedor Yu.; Sidorenko Vlada S. (BIO Web of Conferences)
This article analyses the problem of clustering of innovative mesosystems in the agrarian-industrial complex of Russia in the context of food import substitution strategy. The main emphasis is placed on the identification of factors that hinder the effective development of clusters in the agrarian sphere and the development of recommendations to overcome them. The study was conducted by analysing scientific literature, regulatory legal acts and statistical data. The results show that, despite the active promotion of the cluster approach, the overall level of innovation activity in agriculture remains low. It is revealed that the formal approach to the creation of clusters, lack of trust between the participants, lack of qualified personnel and lack of clear criteria for performance evaluation are the key problems. It is concluded that it is necessary to reorient state policy to support self-organisation of business, development of regional autonomy, stimulation of cooperation and investment in human capital.